PERANCANGAN SISTEM PENDATAAN USAHA MIKRO KECIL MENENGAH UMKM MENGGUNAKAN FRAMEWORK LARAVEL DI DESA BOJONG INDAH KECAMATAN PARUNG - Budi Apriyanto; Bagas Setiyaki Wicaksono; Uliyatunisa (Journal of Research and Publication Innovation, 2026)
Bojong Indah Village is a village located in Parung District, Bogor Regency, West Java Province. This village has not utilized information technology in processing MSME (UMKM) data, resulting in a lack of security, long data collection times, data irregularity, and limitations in retrieving information. The lack of database system utilization also has the potential to cause data loss. Therefore, system development is needed to facilitate MSME data processing to improve services. The purpose of this study is to provide proposals in the form of input or ideas for improving the MSME data management system so that it can support the creation of good data management by utilizing advances in information and communication technology. This study resulted in a web-based population data information system. This system effectively manages population data in a structured and user-friendly manner. The advantages of this system include automated and efficient population data management, reducing human error and management time.